The effectiveness of the quality of women’s performance in NGOs In the city of Mecca, Jeddah and Taif - khalefa, Heba Ahmed Abdulltef (Journal of Humanities & Social Sciences, 2020)
The study aimed to identify the effectiveness of the quality of performance of women in NGOs. The results showed that the quality of the performance of women in NGOs was determined by the study sample (Speed ​​of service delivery, development and improvement of services provided, continuity in service delivery, service delivery method, cooperation with members of NGOs. Cooperation with citizens to meet their needs). She also showed professional proposals to increase the effectiveness of the quality of women’s performance in NGOs. The results reached a suggested concept to increase the researcher used the descriptive method suitable for the social survey method using a comprehensive questionnaire based on the questionnaire as a data collection tool. Data will be coded and analyzed statistically using SPSS.V. 21.0